La aplicación de mensajería WHATSAPP y las culturas periodísticas de los reporteros de la ciudad de Latacunga - De la Cruz Chicaiza, Jonathan Bladimi (2020)
This research project was carried out based on the need to clearly demonstrate the information and evolution in the work of the members of the WhatsApp group “Gober Cotopaxi - Media”. The objective is to describe changes in the journalistic practices of the reporters of the city of Latacunga who exchange messages with official sources through the WhatsApp messaging application. The study methodology is qualitative and quantitative, in which the participant observation technique and interviews were used, which was based on observation sheets in a personalized way, in a certain period of time and these answers are clear, precise and concise. The results obtained allowed to identify the change in the journalistic work that exists at the time of receiving and sending information by WhatsApp, considering that the communication culture has undergone transformations, before the communication professionals went out in search of information and were in the place of the facts, now the news arrives immediately, without any restriction in the WhatsApp group and they have modified their work based on this communication tool. After analyzing the responses of the interviews, it is detected that there is modification when producing information; they say they are plagiarized, misunderstood and even increased in their textual content and testimony. Reason why it is considered that this work will remain as a legacy for future generations knowing that the areas are different, but with a purpose that is to report front page no matter what technology is available to the journalist. The term of journalistic cultures focuses on the importance of human values in the work of the journalist or reporter at the time of reporting, which is based on filling in the gaps in terms of news that people in the urban and rural areas should know